Optimization of fibrolytic enzyme production by Aspergillus japonicus C03 with potential application in ruminant feed and their effects on tropical forages hydrolysis - Facchini, Fernanda D. A.; Vici, Ana C.; Benassi, Vivian M.; Freitas, Luiz A. P.; Reis, Ricardo A. [UNESP]; Jorge, João A.; Terenzi, Hector F.; Polizeli, Maria de Lourdes T. M. (Springer, 2011)
Fibrolytic enzyme production by Aspergillus japonicus C03 was optimized in a medium containing agro-industrial wastes, supplemented with peptone and yeast extract. A 2 3 full factorial composite and response surface methodology were used to design the experiments and analysis of results. Tropical forages were hydrolyzed by A. japonicus C03 enzymatic extract in different levels, and they were also tested as enzymatic substrate. Optimal production to xylanase was obtained with soybean bran added to crushed corncob (1: 3), 0.01% peptone, and 0.2% yeast extract, initial pH 5.0, at 30 degrees C under static conditions for 5 days of incubation. Optimal endoglucanase production was obtained with wheat bran added to sugarcane bagasse (3: 1), 0.01% peptone, and 0.2% yeast extract, initial pH 4.0, at 30 degrees C, for 6 days, under static conditions. Addition of nitrogen sources as ammonium salts either inhibited or did not influence xylanase production. This enzymatic extract had a good result on tropical forage hydrolyzes and showed better performance in the Brachiaria genera, due to their low cell wall lignin quantity. These results represent a step forward toward the use of low-cost agricultural residues for the production of valuable enzymes with potential application in animal feed, using fermentation conditions.
Keywords: Fibrolytic enzymes; Aspergillus japonicus C03; Response surface methodology; Tropical forages; Pretreatment